Between the Square and the Pentagram: Some Reflections on the Music and Architecture of the Old Ouro Preto - М. Flávio Chagas Fonseca (Ибероамериканские тетради, 2024)
Architecture and music have existed organically in Ouro Preto since the very foundation of this town. Since the end of the 16th century, when gold and diamonds wеre discovered and poured into the treasury of the town and into the hands of gold miners, and throughout all the 18th century, the arts flourished in Ouro Preto. This phenomenon was expressed primarily in architecture, but musical practices also developed. The first settlements of the Portuguese bandeirantes, who arrived in those parts of the country from the coast, driven by the gold rush, saw the foundation of Catholic chapels, then pompous churches in the style of colonial Baroque and Rococo were built, where religious music could be heard during church services. Musical compositions created by local composers from Minas Gerais stylistically did not go in line with architectural transformations of the town space and rich decoration of buildings. However, the complementary relations between architectural and musical discourses, as well as their impact on national society and history have led to the creation of a unique cultural heritage, which is preserved today in Ouro Preto.